Optical Characterization of Ferric-Doped ZnO Thin Film Deposited By Chemical Bath Deposition Method - Shahjahan, Mohammad; Eseta, Aktarunnahar; Haque, Mohammad Asadul (BULETIN FISIKA; Vol 25 No 1 (2024): BULETIN FISIKA February EditionDO - 10.24843/BF.2024.V25.i01.p15, 2024)
Fe-doped ZnO holds numerous potential uses in devices such as UV light emitters, piezoelectric transducers, transparent electronics in solar cells, and bright windows as an II-VI semiconductor material. This study looked into the band gap, surface characteristics, optical transmittance, and absorbance of ZnO thin films with Fe doping in different pH conditions such as 8, 9, and 10. The films were prepared using the chemical bath deposition (CBD) method at 350 °C on a glass substrate. The samples were characterized using UV-visible spectroscopy and scanning electron microscopy (SEM). The SEM images of the undoped samples exhibited a lack of cracks, but the doped samples displayed visible cracks due to the presence of Fe in the films. ZnO thin-film surface shape is altered by pH and Fe doping variations. There is a tendency for the films' visual transmission to decrease when the pH rises. The absorbance for all samples increases in the UV and declines in the visible. Fe doping causes the optical band gap Eg to drop. The band gap of both doped and undoped samples reduces when pH rises.